Stable platelet production via the bypass pathway explains long-term hematopoietic stem cell reconstitution - Shoya Iwanami; Toshiko Sato; Hiroshi Haeno; Longchen Xu; Keimyo Imamura; Jun Ooehara; Xun Lan; Hiromitsu Nakauchi; Shingo Iwami; Ryo Yamamoto (iScience)
Summary: In vivo differentiation pathways into several blood cell lineages of Hematopoietic stem cells (HSCs) remain challenging to track over time. Using data from single-cell transplantation assays and mathematical modeling, we examined HSC differentiation kinetics, including the myeloid bypass pathway. We found that myeloid cell production was unchanged with age, whereas B cell production declined, quantitatively confirming myeloid lineage skewing. Estimated dependence on the platelet-bypass correlated with the long-term reconstitution capacity of HSCs. Time-dependent blood cell production patterns calculated by our model distinguished the reconstitution potential of HSCs into subgroups, suggesting a link between the bypass pathway and the multilineage differentiation dynamics of HSCs. Notably, platelet bypass dependence could be determined by the platelet-to-erythrocyte chimerism ratio at 8 weeks after transplantation, serving as a predictive indicator of long-term HSC function. These findings provide quantitative insights into HSC aging and differentiation dynamics, emphasizing the role of the bypass pathway in defining HSC properties.